The polarization of literary censorship in the U.S - Adam Szetela; Shiyu Ji; Michael Walton Macy (PLoS ONE, 2025)
Literary censorship is not new, but the recent resurgence in the U.S. differs from earlier post-war controversies, many of which were bipartisan and focused on protecting children from exposure to sexual and graphic material. Current censorship controversies in the U.S. appear to be much more partisan and ideological, focused on protecting children from politically offensive ideas. Anecdotally, the political right is portrayed as attacking literature in the name of conservative values like preserving the traditional family from alternative expressions of sexuality and sexual preference, with the left targeting material regarded as contrary to progressive values like tolerance of diverse cultural identities. However, these ideological rationales largely reflect the rhetoric of political activists and have not been empirically tested among the broader public. We conducted two studies designed to measure the polarization of support for literary censorship among the voting-age population of the U.S. Surprisingly, both studies cast doubt on the ideological divisions apparent in activist rhetoric. The survey findings from Study 1 indicate widespread opposition to literary censorship that spans ideological divisions, but both liberals and conservatives were more inclined to support censorship of materials that deviated from their respective values and beliefs. The experiment in Study 2 revealed differences in participants’ responses to liberal and conservative criticisms but little difference in the attitudes of liberal and conservative participants. However, liberals were marginally more likely than conservatives to agree with ideologically aligned literary criticism.